Some adaptations of the anthocerophyte Megoceros pellucidus (Colenso) E.A.Hodgs. to extremely low light environments : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Plant Biology at Massey University, Palmerston North, New Zealand - Watkins, Roger Lionel Sloane (Massey University, 2002)
The New Zealand Anthocerophyte Megaceros pellucidus (Colenso) is found in wet, cool temperate rain forest and is associated with extremely low light habitats (0.5-7 μmoles photons m−² s−¹). The light available to M. pellucidus was found to be only 0.2% of the overhead crown canopy light and was heavily attenuated after passing through many leaf canopies. This thesis shows that the photon flux density in these extremely low light habitats can be augmented by two additional light sources, sunfleck light, especially at midday, and light reflected from adjacent water surfaces, such as rivers or ponds, as the sun's incident ray path angle diminishes late or early in the day. This thesis looks at some of the strategies M. pellucidus uses to survive in its low light habitat and, in adapting to acquire such sensitivity to low light parameters, how M. pellucidus protects itself from photoinhibition if exposed to high white light of more than 140 μmoles photons m−² s−¹or blue (470 nm) light of more than 3 μmoles photons m−² s−¹. The chloroplast position in M. pellucidus, when in its normal habitat, was found to retain an expanded form situated on the periclinal cell wall proximal to the light source (an epistrophe position). When thallus tissue sections of M. pellucidus were irradiated with blue light of more than 3 μmoles photons m−² s−¹ or white light of more than 140 μmoles photons m−² s−¹ the chloroplast shrank dramatically and assumed a position on anticlinal walls (a parastrophe position). Red (662 nm) light of less than 130 μmoles photons m−² s−¹ or darkness had no obvious effect on the morphology epistrophe chloroplasts, but this treatment resulted in the chloroplasts expanding and moving back to the epistrophe position after irradiation by blue or high levels of white light. Based on the rate of volume change occasioned when the chloroplasts were irradiated with blue, white, red light or darkness it was concluded that a water flux was induced across the membranes of the various intracellular organelles that depended on the wavelength of the light and the photon flux density. Various concentrations of polyethylene glycol-20 (PEG) were used as an osmoticum and induced chloroplast shrinkage to an extent and at a rate similar that induced by blue light. Red (662 nm) light of 130 μmoles photons m−² s−¹, was observed to expand the chloroplast volume against the osmotic gradient, while darkness had no effect. A comparison of transmission electron microscope (TEM) micrographs taken of both blue / high light conditions and dark or red irradiated chloroplasts show differences in thylakoid membrane architecture, the dark-exposed samples having a loose open form with pseudograna and greater areas of stroma compared to the blue and high light samples that showed a tight compression of the thylakoids and very reduced areas of stroma. Large numbers of starch granules were apparent in all but the blue irradiated TEM micrographs. Examination of the micrographs showed there were obvious differences between the size of the starch granules (TEM, x7800, micrographs having starch granules with a dark to light ratio of 2.165) as well as in the texture and density.
Keywords: Adaptation; Effect of light; New Zealand -- North Island; Hornworts (Bryophytes)